THE EFFECT OF EXCHANGE RATES AND SYSTEMATIC RISK ON SUKUK VALUES IN THE ISLAMIC CAPITAL MARKET IN 2020-2022 - Nurfaiza Nurfaiza; Romi Iskandar; Wushi Adilla Arsy (Jurnal Scientia, 2023)
An exchange rate (exchange rate) is an agreement known as a currency exchange rate against a current or future payment, between two currencies of each country or region. In addition, Sukuk also implies ownership claims, potentially increasing the company's systemic risk. Conventional bonds are believed to be less risky than sharia-compatible sukuk, but sukuk can still impact a company's systemic risk. Risk can be measured using the stock beta coefficient, which measures the return volatility of a security or portfolio return on market returns. Regarding a security’s beta, it is important to analyze securities or portfolios. This study aims to determine the exchange rate and systematic risk together (simultaneously) on the value of Islamic bonds in the Islamic capital market. This study used a sample of 24 companies with a sampling technique that is Totality Sampling. The data analysis technique used is panel data regression, classical assumption test, autocorrelation test, partial T test, simultaneous F test, and the R2 determinant test. The study results show that the independent variable X1 (exchange rate) is 2.069452. It is accepted if it is seen from the probability value equal to 0.0042, which is smaller than 0.05 Ha. It significantly negatively affects the company's Sukuk Value in the Islamic Capital Market. Variable X2 (Systematic Risk) is 0.721231, then when viewed from the probability value equal to 0.0321 which is <0.05 then H0 is rejected and Ha is accepted. Systematic risk (X2) has a significant effect on the value of Sukuk. The calculated F value is 18.4226 while the F table with a level of α = 5% is 2.66. Thus F count > F table (18.4226 > 2.66), indicates that there is a significant influence between the Exchange Rate (X1) and Systematic Risk (X2) variables simultaneously on the Sukuk Value